The Use of Problem Based Learning Models to Improve Student Learning Outcomes at SD Negeri 18 Ampang Gadang - Pribadi, Anggun (MANDAILING GLOBAL EDUKASIA, 2024)
This study aims to improve student learning outcome in Islamic religious education learning using the problem based learning model. This study is a classroom action research that uses four steps, namely planning, action, observation and reflection. The subjects of this study were junior high school students. The data for this study were obtained by test and observation techniques. Tests are used to measure learning outcomes and observations are used to analyze teacher and student learning activities. The data analysis technique used in this study is descriptive statistics by comparing the results obtained with indicators of research success. The results of the study indicate that the problem based learning model can improve student learning outcome in Islamic religious education learning. This can be seen from the increase in the percentage of student learning completion in each cycle with details of the pre-cycle 52.18%, the first cycle 67.07% and in the second cycle it increased to 90.12%. Thus, the use of problem based learning model can be used as an alternative to improve student learning outcome in Islamic religious education learning.